Operating Leverage, Profitability, and Capital Structure - Chen, Zhiyao; Harford, Jarrad; Kamara, Avraham (Journal of Financial and Quantitative Analysis, 2019)
Operating leverage increases profitability and reduces optimal financial leverage. Thus, operating leverage generates a negative relation between profitability and financial leverage that is thought to be inconsistent with the trade-off theory but is commonly observed in the data. We demonstrate the effect of operating leverage on firms’ profitability and financial leverage, as well as on the empirical relation between profitability and financial leverage, by using China’s entry into the World Trade Organization in 2001 and its effect on the capital–labor ratio of U.S. firms.